Politeness in Javanese daily conversations: A sociolinguistic analysis in Temanggung - Aji Dwi Noviantoro; Didit Kurniadi; Indah Arvianti (Early Publishing Group, 2026)
This study investigates how politeness is expressed, negotiated, and occasionally violated in Javanese daily conversations in Temanggung, a region undergoing rapid sociolinguistic change due to generational language shift. Using a qualitative descriptive approach, natural conversations were collected from 15 interactional events involving speakers of different ages and social relationships. The data were analyzed using a sociolinguistic lens, focusing on Javanese speech levels (Ngoko, Krama, Krama inggil) and politeness frameworks proposed by Brown and Levinson as well as Leech’s politeness maxims. The findings show that younger speakers increasingly rely on Ngoko Lugu in situations where Krama is traditionally expected, particularly when speaking with older interlocutors or individuals of higher social rank. This mismatch often results from reduced exposure to the whole speech level system and the influence of Indonesian as a dominant everyday code. The analysis also reveals that speakers occasionally use pragmatic strategies (such as honorific terms, indirectness, or softening particles) to compensate for limited mastery of Krama. These patterns indicate a shift in how politeness is performed and interpreted in contemporary Javanese interactions. The study highlights the need for sustained cultural and educational efforts to maintain speech level competence as a key component of Javanese linguistic identity..